Delayed haemorrhage and pseudoaneurysms following liver trauma. - Henry, Luke; Fischer, Nicholas (European Journal of Trauma & Emergency Surgery, 2022)
Background: Delayed Haemorrhage (DH) is a potential complication following liver trauma. Hepatic artery pseudoaneurysms (HAPAs) are also a frequently considered delayed complication of liver trauma, yet their incidence is rare. Furthermore, little is known about their natural history, with some observed to resolve spontaneously. Some authors postulate that DH following liver trauma may in fact originate from HAPAs. Aim: To investigate the incidence of DH and HAPA following liver trauma, review subsequent management and explore a possible association between the two. Methods: A retrospective study of liver trauma over a 14 year period at a trauma centre, including a case–control analysis comparing patients with DH and HAPA to liver injury grade matched controls. Results: 450 patients were admitted with liver trauma of which 10 patients had DH (2.2%) and 7 HAPA (1.6%). Both DH and HAPA patients had significantly greater blood transfusion requirements, lower haemoglobin (Hb) levels and a greater Hb decrease compared to controls. No patient with an HAPA had a large volume of haemoperitoneum on imaging, and there were no patients in the clinical DH group with previous or concurrent HAPA identified, and no deaths in either group. Conclusion: DH and HAPA following liver trauma are rare. DH following liver trauma was not associated with HAPA on imaging. This study shows that HAPAs cause ongoing insidious bleeding and Hb decline, but we did not find evidence to support the commonly held perception of a risk of 'rupture' and catastrophic haemorrhage.